The Role of Pancasila and Citizenship Education Subjects in Developing a Democracy Culture - Arifin Arifin (BIRCU, 2022)
The subject of Pancasila and Citizenship Education is one of the compulsory subjects taught to students to create citizens in accordance with what is mandated by Pancasila and the 1945 Constitution. As one of the places designated to develop democratic values for participants for students, schools do play an important role in shaping a democratic culture through various learning methods in the classroom and extracurricular activities. But furthermore, the democratic culture that occurs in the school environment is functioned to get used to living in deliberation in uniting opinions, solving problems and responding to differences through an attitude of equality, cooperation, tolerance and brotherhood. This study uses a normative juridical method, namely legal research that refers to written regulations or other legal materials, including statutory approaches, case approaches and conceptual approaches, while the results of this study explain that learning Pancasila and Citizenship education is an activity that This is done consciously and intentionally in the teaching and learning process through the discussion method, related to this, that democratic values in learning are very important to be instilled in every student, especially in good behavior or in accordance with what has been applied in the values democracy, so that it can build and develop human potential with high character, integrity in expressing opinions, and having effective competence. Basically, the implementation of democratic values provides an opportunity for all students to be able to express their opinions regarding the subject matter that has been conveyed, this is one way to implement democratic values in Pancasila and civics education lessons (PPKn), so that students can understand and at the same time apply it in everyday life. Furthermore, on the same occasion, students are also required to be able to develop an attitude of mutual respect and appreciation both to all students and to teachers.